Lack of amino acids in mouse hepatocytes in culture induces the selection of preneoplastic cells - Chisari, Andrea Nancy (2012)
Protein malnutrition occurs when there is insufficient protein to meet metabolic demands. Previous works have indicated that cycles of protein fasting/refeeding enhance the incidence of early lesions during chemical carcinogenesis in rat liver. The general objective of this work was to study the effect of aminoacids (Aa) deprivation on the proliferation and survival of hepatocytes, to understand its possible involvement in the generation of pre-neoplastic stages in the liver. Lack of Aa in the culture medium of an immortalized mice hepatocyte cell line induced loss in cell viability, correlating with apoptosis. However, a subpopulation of cells was able to survive, which showed a more proliferative phenotype and resistance to apoptotic stimuli. Escaping to Aa deprivation-induced death is coincident with an activated mTOR signaling and higher levels of phospho-AKT and phospho-ERKs, which correlated with increased activation of EGFR/SRC pathway and overexpression of EGFR ligands, such as TGF-α and HB-EGF. Lack of Aa induced a rapid increase in reactive oxygen species (ROS) production. However, cells that survived showed an enhancement in the levels of reduced glutathione and a higher expression of γ-GCS, the regulatory enzyme of glutathione synthesis, which can be interpreted as an adaptation of the cells to counteract the oxidative stress. In conclusion, results presented in this paper indicate that it is possible to isolate a subpopulation of hepatocytes that are able to grow in the absence of Aa, showing higher capacity to proliferate and survive, reminiscent of a preneoplastic phenotype.